2014
DOI: 10.1111/spol.12076
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Personal Social Services – TheIsraeli Experience

Abstract: The current article explores the aspects of regulatory policy in the field of personal social services. In Israel, the government sets standards, and finances and oversees personal social services, while the services themselves are provided primarily by non-governmental organizations. Based on a qualitative study we examined two questions. First, what characterizes the implementation of regulatory mechanisms in the field of personal social services in Israel? Second, how can we explain the outcomes of regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In such a regulatory system, finding the right relational distance between the inspectors and the inspected homes is a major challenge: How can the inspector be close enough to ensure that the homes are truly committed to the goals of the YPA and promote learning and improvement, without being too close and jeopardising the integrity of the regulatory process? As mentioned, the respondents were aware of this problem, and the same issues appear in previous studies (see Lahat & Talit, ; Spiro & Fromer, ).…”
Section: Discussion: a Learning‐based Approach To Regulationsupporting
confidence: 68%
See 2 more Smart Citations
“…In such a regulatory system, finding the right relational distance between the inspectors and the inspected homes is a major challenge: How can the inspector be close enough to ensure that the homes are truly committed to the goals of the YPA and promote learning and improvement, without being too close and jeopardising the integrity of the regulatory process? As mentioned, the respondents were aware of this problem, and the same issues appear in previous studies (see Lahat & Talit, ; Spiro & Fromer, ).…”
Section: Discussion: a Learning‐based Approach To Regulationsupporting
confidence: 68%
“…Given the greater reliance on non‐governmental agencies for the delivery of personal social services, the regulatory role of the Ministry of Welfare has increased significantly (Lahat & Talit, ; Spiro & Fromer, ). The regulatory systems of the Ministry were established long before contracting‐out became so widespread, and the role of the inspectors, most of whom were social workers, was developed along the lines of supervision within the social work profession (Hovav, ).…”
Section: The Israeli Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Contracting (out) and price‐driven procurement have been shown to impact upon working conditions (Campbell & Peeters, ; Dube & Kaplan, ; Flecker & Hermann, ; Engström & Axelsson, ; Grimshaw et al, , p. 1; Vrangbæk et al, ), which may, in turn, affect the quality of service (Apostolou, , p. 217; Benjamin, ; Grimshaw et al, : X, 37). With a growing importance of contracting of services, public contracts play an indispensable role in setting standards (Lahat & Talit, , p. 336) and an increasingly important role as a tool in the regulation of labour (Holley, ).…”
Section: Resultsmentioning
confidence: 99%
“…Research on contracting out and public contracting of services has suggested that these developments have important implications for working conditions and the quality of services (Benjamin, ; Dube & Kaplan, ; Engström & Axelsson, ; Flecker & Hermann, ; Grimshaw, Cartwright, Keizer, & Rubery, ; Vrangbæk, Petersen, & Hjelmar, ). With the growing importance of public contracting, public contracts increasingly act as tools for defining standards of services (Lahat & Talit, , p. 336) and regulating labour standards and working conditions (Holley, ). Yet, despite their importance as a regulatory tool, little is known about public authorities' strategies to warrant decent working conditions and a high quality of services when tendering.…”
Section: Introductionmentioning
confidence: 99%